Locking and Unlocking the Molecular Spin Crossover Transition. Issue 39 (28th August 2017) - Zhang, Xin; Costa, Paulo S.; Hooper, James; Miller, Daniel P.; N'Diaye, Alpha T.; Beniwal, Sumit; Jiang, Xuanyuan; Yin, Yuewei; Rosa, Patrick; Routaboul, Lucie; Gonidec, Mathieu; Poggini, Lorenzo; et al.
Abstract: The Fe(II) spin crossover complex [FeH2 B(pz)2 2 (bipy)] (pz = pyrazol‐1‐yl, bipy = 2, 2′‐bipyridine) can be locked in a largely low‐spin‐state configuration over a temperature range that includes temperatures well above the thermal spin crossover temperature of 160 K. This locking of the spin state is achieved for nanometer thin films of this complex in two distinct ways: through substrate interactions with dielectric substrates such as SiO2 and Al2 O3, or in powder samples by mixing with the strongly dipolar zwitterionic p ‐benzoquinonemonoimine C6 H2 (—⋯ NH2 )2 (—⋯ O)2 . Remarkably, it is found in both cases that incident X‐ray fluences then restore the [FeH2 B(pz)2 2 (bipy)] moiety to an electronic state characteristic of the high spin state at temperatures of 200 K to above room temperature; that is, well above the spin crossover transition temperature for the pristine powder, and well above the temperatures characteristic of light‐ or X‐ray‐induced excited‐spin‐state trapping. Heating slightly above room temperature allows the initial locked state to be restored. These findings, supported by theory, show how the spin crossover transition can be manipulated reversibly around room temperature by appropriate design of the electrostatic and chemical environment. Abstract : Locking of the spin state of a molecular spin crossover system has been achieved, and room‐temperature optical isothermal switching from a low spin to high spin state is demonstrated. Key ingredients necessary for a room temperature molecular magnetoelectric are now realizable.